PENGARUH PENERAPAN MODEL KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII MTSS MUHAMMADIYAH PANGKALAN - Sari, Fika Rosita (Jurnal Edukasi dan Penelitian Matematika, 2025)
Learning outcomes are one of the determinants of learning success. MTsS Muhammadiyah class VIII learning outcomes are low. The low level of student participation in the educational process is one of the main causes. One method to overcome implementation problems is the Two Stay Two Stray (TSTS) learning model. The aim of the research is to find out whether students whose mathematics learning uses the TSTS type cooperative learning model achieve superior learning outcomes compared to students using the direct learning model. Statistical group design combined with quasi-experimental design. Population of Class VIII MTsS Muhammadiyah Based on the 2023–2024 Academic Year. The experimental class is VIII–1, and the control class is VIII–2. Essay as a tool for testing research. T-test analysis was performed on the data. The results of the analysis show that the P t test is 0.016 (α) = 0.05. P-value < α indicates that class VIII students at MTsS Muhammadiyah Pangkalan apply the TSTS type cooperative learning model with higher learning outcomes than direct learning.Keywords– Mathematics Learning Outcomes, Direct Learning Model, Cooperative Learning Model Type Two Stay Two Stray